Pemanfaatan Cangkang Kelapa Sawit dan Tempurung Kelapa Menjadi Biopelet dengan Variasi Jenis Perekat - Naswa Amalia Ananda; Sirajuddin Sirajuddin; Arinda Ramadani (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The availability of biomass waste in the form of palm kernel shells and coconut shells in East Kalimantan is high due to the increase in palm oil and coconut production, but its utilization is still not optimal, so further processing is needed to increase its economic value. One way to utilize this waste is to process it into biopellets as a renewable fuel. The main problem in production biopellets lies in the selection of the type of binder that affects the quality characteristics of the biopellets. This study aims to analyze the effect of variations in the type of binder on the characteristics of biopellets made from a mixture of palm kernel shells and coconut shells with a ratio of 2:1. The research method included the biopellet production process using the pelletizing method with variations in adhesive types, namely cornstarch, sago flour, glutinous rice flour, tapioca flour, and molasses, with the parameters analyzed including proximate analysis and calorific value. The best results were obtained from biopellets with sago flour adhesive with a moisture content of 9.44%, ash content of 1.65%, volatile matter of 71.32%, fixed carbon of 17.59%, and calorific value of 19.601 MJ/kg.